Designing anti-diabetic ß-cells microcapsules using polystyrenic sulfonate, polyallylamine and a tertiary bile acid: Morphology, bioenergetics and cytokine analysis. - Mooranian, A.; Negrulj, R.; Morahan, G.; Jamieson, E.; Al-Salami, Hani (2016)
Purpose: Recently sodium alginate (SA)-poly-l-ornithine (PLO) microcapsules containing pancreatic β-cells that showed good morphology but low cell viability (<27%) was designed. In this study, two new polyelectrolytes, polystyrenic sulfonate (PSS; at 1%) and polyallylamine (PAA; at 2%) were incorporated into a microencapsulated-formulation, with the aim of enhancing the physical properties of the microcapsules. Following incorporation, the structural characteristics and cell viability were investigated. The effects of the anti-inflammatory bile acid, ursodeoxycholic acid (UDCA), on microcapsule morphology, size, and stability as well as β-cell biological functionality was also examined. Methods: Microcapsules were prepared using PLO-PSS-PAA-SA mixture and two types of microcapsules were produced: without UDCA (control) and with UDCA (test). Microcapsule morphology, stability, and size were examined. Cell count, microencapsulation efficiency, cell bioenergetics, and activity were also examined. Results: The new microcapsules showed good morphology but cell viability remained low (29% ± 3%).UDCA addition improved cell viability post-microencapsulation (42 ± 5, P < 0.01), reduced swelling (P < 0.01), improved mechanical strength (P < 0.01), increased Zeta-potential (P < 0.01), and improved stability. UDCA addition also increased insulin production (P < 0.01), bioenergetics (P < 0.01), and decreased β-cell TNF-α (P < 0.01), IFN-gamma (P < 0.01), and IL-6 (P < 0.01) secretions. Conclusions: Addition of 4% UDCA to a formulation system consisting of 1.8% SA, 1% PLO, 1% PSS, and 2% PAA enhanced cell viability post-microencapsulation and resulted in a more stable formulation with enhanced encapsulated β-cell metabolism, bioenergetics, and biological activity with reduced inflammation. This suggests potential application of UDCA, when combined with SA, PLO, PSS, and PAA, in β-cell microencapsulation and diabetes treatment.